Numerical simulation of two-track laser hardening process of 42CrMo steel. Issue 1 (31st December 2022) - Daming, Tong; Ziyang, Zhang; Zhuguo, Li; Jianfeng, Gu; Sijia, Li; Qunli, Zhang; Chuanwei, Li; Junyu, Zhao; Zhaonan, Hu
ABSTRACT: In this study, a thermal–phase–mechanical coupled numerical model was presented for the prediction of the distribution of temperature, phase and residual stress of 42CrMo steel during two-track laser hardening process. Austenite and tempering transformation were simulated based on the isoconversional method. K-M equation was used to calculate the fraction of martensite. Residual stress was calculated considering the thermal strain, transformation strain and transformation plasticity. The accuracy of the numerical model was verified according to the comparison with experimental results. The stress distribution of two-track laser hardening process was studied according to numerical simulation results. And the effect of the second track on the residual stress produced by the first track in two-track laser hardening was also analyzed by using this numerical model.